INNOVATIVE APPROACHES TO STRENGTHENING COMMUNICATIVE COMPETENCE IN HIGHER EDUCATION (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Globalization and digital transformation processes are placing new demands on the higher education system. A specialist who can successfully operate in a market economy must not only have knowledge in his field, but also have a high level of communicative competence. Communicative competence is the ability of a person to effectively communicate with himself, the team and the environment, to clearly express his thoughts, argue, listen and adapt to various social situations. The use of innovative approaches to strengthen this competence in higher education is becoming an increasingly relevant issue. This thesis analyzes the role of modern innovative pedagogical technologies, digital tools and interactive methods in the development of communicative competence.